Children and youth with non-traumatic brain injury: a population based perspective. Issue 1 (December 2016) - Chan, Vincy; Pole, Jason; Keightley, Michelle; Mann, Robert; Colantonio, Angela
Abstract Background Children and youth with non-traumatic brain injury (nTBI) are often overlooked in regard to the need for post-injury health services. This study provided population-based data on their burden on healthcare services, including data by subtypes of nTBI, to provide the foundation for future research to inform resource allocation and healthcare planning for this population. Methods A retrospective cohort study design was used. Children and youth with nTBI in population-based healthcare data were identified using International Classification of Diseases Version 10 codes. The rate of nTBI episodes of care, demographic and clinical characteristics, and discharge destinations from acute care and by type of nTBI were identified. Results The rate of pediatric nTBI episodes of care was 82.3 per 100, 000 (N = 17, 977); the average stay in acute care was 13.4 days (SD = 25.6 days) and 35 % were in intensive care units. Approximately 15 % were transferred to another inpatient setting and 6 % died in acute care. By subtypes of nTBI, the highest rates were among those with a diagnosis of toxic effect of substances (22.7 per 100, 000), brain tumours (18.4 per 100, 000), and meningitis (15.4 per 100, 000). Clinical characteristics and discharge destinations from the acute care setting varied by subtype of nTBI; the proportion of patients that spent at least one day in intensive care units and the proportion discharged home ranged from 25.9 % to 58.2 % and from 50.6 % to 76.4 %, respectively. Conclusions Children and youth with nTBI currently put an increased demand on the healthcare system. Active surveillance of and in-depth research on nTBI, including subtypes of nTBI, is needed to ensure that timely, appropriate, and targeted care is available for this pediatric population.